FORMULASI SEDIAAN SABUN CAIR EKSTRAK LIDAH BUAYA (Aloe vera L.) - Mahayuni, Made Galih Dwi; Putra, I Gusti Ngurah Agung Windra Wartana; Wintariani, Ni Putu (Jurnal Riset Kefarmasian Indonesia, 2023)
Skin is the external part of body which protects internal organs from external interference, such as bacteria, viruses, cold air, hot sun, exposure to UV radiation, pressure, etc. Maintain clean skin is an important thing to do to prevent skin diseases. The way to keep our skin clean is use a mild soap which is good for the skin. Soap is one of the preparations commonly used in daily life. The ingredients of liquid soap are made up of surfactants, thickeners, preservatives and pH regulators. The presence of surface-active agents in soap is important for cleansing the dirt from the skin. Thickeners are important in the soap to obtain the required viscosity of the formulation. The aim of this study was to determine the characteristics of aloe vera (Aloe Vera L.) liquid soap. This type of research is an experimental study with a completely randomized design. The formula will be tested for physical and chemical properties which include organoleptic tests, viscosity tests, specific gravity tests, foam stability tests, and pH tests. Aloe vera liquid soap in all formulas has physical and chemical characteristics that meet the standards where the viscosity values obtained are 2616-4188 cP, specific gravity 1.067-1.082, foam resistance 61-70%, and pH 6.1-7